2010
DOI: 10.1007/s00347-010-2198-4
|View full text |Cite
|
Sign up to set email alerts
|

Kontinuierliche 24-h-Aufzeichnung von Augendruckschwankungen mittels drahtlosem Kontaktlinsensensor Triggerfish™

Abstract: For the first time a practicable, well tolerated, non-invasive device for continuous 24 h monitoring of changes of the corneal curvature due to changes of the intraocular pressure is available. It is not a direct measurement of the intraocular pressure. The resulting profile gives additional information about the behaviour of the intraocular pressure, especially during out-of-office times and night times. Disadvantages are the high cost of the contact lens sensor and the lack of validation of the results and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…A similar implantable device also has been described for monkeys [35], and a less invasive prototype has been described for rabbits utilizing a 30 g needle in the vitreous cavity [36]. Recently, a telemetric contact lens sensor (SENSIMED Triggerfish ® ) has been used in humans to frequently measure IOP over a 24 h period [33,37]. This device has demonstrated that IOP is very dynamic and that measurements at just a few time points may not fully reflect the physiologic changes in IOP [33,37].…”
Section: Continuous Iop Measurementsmentioning
confidence: 97%
See 2 more Smart Citations
“…A similar implantable device also has been described for monkeys [35], and a less invasive prototype has been described for rabbits utilizing a 30 g needle in the vitreous cavity [36]. Recently, a telemetric contact lens sensor (SENSIMED Triggerfish ® ) has been used in humans to frequently measure IOP over a 24 h period [33,37]. This device has demonstrated that IOP is very dynamic and that measurements at just a few time points may not fully reflect the physiologic changes in IOP [33,37].…”
Section: Continuous Iop Measurementsmentioning
confidence: 97%
“…Recently, a telemetric contact lens sensor (SENSIMED Triggerfish ® ) has been used in humans to frequently measure IOP over a 24 h period [33,37]. This device has demonstrated that IOP is very dynamic and that measurements at just a few time points may not fully reflect the physiologic changes in IOP [33,37]. The device does not, however, measure IOP per se but instead measures relative changes in IOP in arbitrary units which cannot be easily translated into absolute IOP values [33,37].…”
Section: Continuous Iop Measurementsmentioning
confidence: 97%
See 1 more Smart Citation
“…Die Sensorkontaktlinse Triggerfish (Sensimed, Lausanne, Schweiz) hat für Sicherheit und Verträglichkeit im Jahr 2009 eine CE-Zertifizierung erhalten. Diese beiden Parameter haben sich in einigen Studien als gut erwiesen [6][7][8][9][10]. De Smedt [10] beschrieb die Verträglichkeit der Kontaktlinse bei 10 Normalaugen, während bei den anderen Publikationen Patienten mit okulärer Hypertension und Glaukom eingeschlossen wurden.…”
unclassified
“…Dies wurde kürzlich durch Jonas [48] Zurzeit ist ein kontaktlinsengestützter Augendrucksensor in Entwicklung, der ein ambulantes 24-Stunden-Augeninnendruckprofil ermöglichen soll. Dies ist insofern von großem Interesse, da auch Augendruckwerte unter alltäglichen Belastungssituationen erfasst werden könnten [55]. Diese Technik ist derzeit in der Schweiz bereits auf dem Markt, in Deutschland erfolgen derzeit die Zulassungsstudien in ausgewählten Zentren.…”
unclassified